Mangrove Density And Abundance Of Bivalvia In Sungai Bakau Region Sinaboi Sub Distric Rokan Hilir Regency Riau Province - Renta Elisabet; Adnan Kasry; Nur El Fajri (Ilmu Perairan (Aquatic Science), 2010)
This research was conducted from July - August 2010 in Sungai BakauRegion, Sinaboi Sub Distric, Rokan Hilr Regency, Riau Province. This research aimsto identify spesies mangrove in Sungai Bakau region, lokan abundance and also tounderstand the relationship between mangrove density with abundance of bivalvia.The result showed that 9 species of mangrove were found: Avicennia marina,Avicennia alba, Rhizophora apiculata, R. mucronata, Bruguiera gymnorhyza, Soneratiaalba, S. coseolaris, and Nypa fruticans. Density of mangrove between 743 – 2.001trees/ha. In each stasion, there were 2 kinds of bivalvia such as Polymesoda expansa andPharus sp. The abundance of bivalvia 3.400 – 5.645 organism/m2. The highestabundance was obtained in the 3rd station (5.645 organism/m2), while the lowest was inthe 2nd station (3.400 organism/m2). To found out relation between mangrove densityand bivalvia abundance, the data were analized by using simple linier regretion.Theregression line test between mangrove density with abundance of bivalvia showed theequation Y=686,486 + 2,470 X with determine coefisien (R2) is 0,980.Keyword : mangrove, bivalvia, density, abundance, Sungai Bakau